KARAKTER MAJA LABO DAHU DALAM PERSPEKTIF PENDIDIKAN ISLAM DI BIMA - Abd Salam (Prodi PAI STIT Sunan Giri Bima, 2022)
Maja Labo Dahu is a set of adab based on Islamic education that can control one's attitude and behave politely in every activity of one's life. Maja Labo Dahu is not only a philosophy of the Bima people, not just an expression but as a locomotive for the formation of Islamic education that is civilized, knowledgeable and behaves and speaks well in the family, social and school environment. Maja Labo Dahu has the value of dou mbojo advice, has the value of Education and has the value of Islam. Maja Labo Dahu is an attitude that is used as a basis for life in behaving, thinking, acting, where one must have a sense of shame and fear that is always instilled in the heart. So that Maja Labo Dahu is a source of adab teachings, both in speaking good words, behaving politely and politely, and both spiritually and spiritually. This study focuses on